TI_GERICHTE 32.2019.132 vom 4. Juni 2019 , A torto l'Ufficio AI non entra nel merito della nuova domanda. Rinvio atti - TI Tribunale d'appello (2019)
A torto l'Ufficio AI non entra nel merito della nuova domanda. Rinvio atti